Cordycepin-oxalate as well as preparation method and application thereof

Cordycepsin-oxalate eutectics were prepared by liquid-assisted grinding, which solved the problems of short half-life of Cordycepsin crystal preparation and difficult crystal form, achieved stability and sustained release effects, and had significant medicinal potential.

CN120535562APending Publication Date: 2025-08-26NANJING TECH UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510658834.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-21
Publication Date
2025-08-26

AI Technical Summary

Technical Problem

Cordyceps crystal preparation has a short half-life and is difficult to control crystal form preparation. The existing structural modification process is complex and there are many by-products, making it difficult to achieve effective sustained release.

Method used

Cordycepsin-oxalate eutectics were prepared by liquid-assisted grinding method, and the Cordycepsin-crystalline II crystals were physically mixed and dried under normal pressure to obtain stable Cordycepsin-oxalate eutectics.

Benefits of technology

It improves the stability and dissolution rate of Cordyceps sinensis eutectic salt, realizes the sustained release effect of the drug, and has important potential application value for medicine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120535562A_ABST
    Figure CN120535562A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of medicine crystals, and relates to cordycepin-oxalate as well as a preparation method and application thereof. The invention relates to a preparation method of cordycepin-oxalate. The preparation method comprises the following steps: (1) physical mixing: sufficiently and uniformly mixing oxalic acid and cordycepin-crystal form II crystals; (2) liquid auxiliary grinding: adding an auxiliary agent, and continuously grinding to obtain a solid mixture; and (3) drying the solid mixture to obtain the cordycepin-oxalate. According to the method, the cordycepin-oxalic acid eutectic salt is prepared for the first time, the dissolution rate of the cordycepin-oxalic acid eutectic salt is obviously lower than the dissolution rate of cordycepin reported in the prior art, and the cordycepin-oxalic acid eutectic salt has extremely high potential medicinal application value. The cordycepin-oxalic acid eutectic salt has important technical innovation and market application potential due to the slow release effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pharmaceutical crystals and relates to cordycepin-oxalate and a preparation method and application thereof. Background Art

[0002] Cocrystals are multicomponent materials formed by neutral molecules, a host molecule (API) and a guest molecule (and a second component, a ligand), linked together by non-covalent bonds such as hydrogen bonds or coordination bonds, in a specific stoichiometric ratio. Methods for preparing cocrystals are primarily categorized into three main types: solution-mediated crystallization, solution-free crystallization, and other methods. Solution-mediated crystallization encompasses traditional cooling crystallization, reaction crystallization, and evaporative crystallization, as well as solution-mediated slurry conversion crystallization, high-pressure homogenization (HPH), high-shear granulation (HSG), ultrasound-assisted crystallization, and liquid-assisted grinding (LAG). These methods offer the advantage of rapid and efficient screening of cocrystal ligands. Solvent-free crystallization, primarily dry grinding, hot melt crystallization, spraying (SC), and polymer-assisted grinding, lacks any solvent assistance and prevents solvate formation, is environmentally friendly, but is time-consuming. Other methods include microwave-assisted crystallization, freeze-drying crystallization, electrospray crystallization, laser crystallization, and resonant acoustic hybrid crystallization.

[0003] Cordycepin is also known as cordycepin and cordycepin. Its chemical composition is 3'-deoxyadenosine (3'-dA for short). Its molecular formula is C 10 H 13 N5O3, molecular weight 251.25. Cordycepin belongs to the purine alkaloids. The conjugated structure on the purine ring gives cordycepin strong ultraviolet absorption, with a maximum absorption wavelength of 259.0nm. Cordycepin is soluble in water, hot ethanol and methanol, but insoluble in ether, chloroform and benzene.

[0004]

[0005] As a hot substance in the pharmaceutical field, the preparation of cordycepin into medicine is an irresistible trend. On the one hand, systematic crystal property research and transformation relationship research are needed before the drug is prepared. In order to avoid the recurrence of the "ritonavir crystal form" incident, providing basic crystal form data and preparing stable crystal forms can help cordycepin better exert its pharmacological efficacy; on the other hand, as a typical drug with a half-life of less than 1h, it is obviously not suitable for direct formulation means of sustained release. The structural modification process is complex, and the by-products are numerous and complex and uncontrollable. The study of sustained release of cordycepin co-crystallization is expected to become a means of assisting the sustained release of cordycepin, providing the possibility for the later development of cordycepin medicine or preparation sustained release. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to address the problems in the prior art such as the short half-life of cordycepin crystals and the difficulty in controlling the crystal form preparation. The present invention provides a method for preparing a stable eutectic salt of cordycepin and obtains a eutectic salt with medicinal potential.

[0007] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:

[0008] The present invention discloses a cordycepin-oxalate, wherein the molecular formula of the cordycepin-oxalate is C 10 H 13 N5O3·H2C2O4; the molecular structure of the cordycepin-oxalate is as follows:

[0009]

[0010] Furthermore, the present invention discloses a method for preparing the above-mentioned cordycepin-oxalate, comprising the following steps:

[0011] (1) Physical mixing: Take oxalic acid and cordycepin-crystalline form II crystals and mix them thoroughly;

[0012] (2) Liquid-assisted grinding: Add additives and continue grinding to obtain a solid mixture;

[0013] (3) Drying the solid mixture to obtain cordycepin-oxalate.

[0014] In some embodiments, in step (1), the molar ratio of oxalic acid to cordycepin-form II crystals is 1:1.

[0015] In some embodiments, in step (2), the auxiliary agent is water, 10 vt.% or less ethanol-water solution, or 10 vt.% or less isopropanol-water solution; and / or, the mass of the auxiliary agent is 20% to 70% of the total mass of the oxalic acid and cordycepin monocrystalline form II crystals; and / or, the grinding time is 1.0 to 8.0 h.

[0016] In some embodiments, preferably, in step (2), the mass of the auxiliary agent is 20% to 50% of the total mass of the oxalic acid and cordycepin-crystalline form II crystals, more preferably 20% to 40%, and even more preferably 25% to 35%.

[0017] Wherein, in step (2), the grinding is performed using an agate mortar, and there is no special requirement for the particle size of the crystalline powder obtained by grinding, and the normal crystalline powder size can be used.

[0018] In some embodiments, in step (3), the drying is carried out at normal pressure; and / or, the drying is carried out at 40-60° C.; and / or, the drying time is 8-12 hours.

[0019] In some embodiments, in step (1), the cordycepin crystalline form II crystals are prepared according to the following method:

[0020] The crude cordycepin is mixed with a solvent to obtain a crude cordycepin solution; the crude cordycepin solution is cooled, and the obtained slurry mother liquor is stabilized and crystallized, which is then filtered, the solid is washed, and dried to obtain cordycepin monocrystalline form II crystals.

[0021] In some embodiments, the solvent is water, an isopropanol-water solution of less than 80 vt.%, or an ethanol-water solution of less than 10 vt.%; and / or the crude cordycepin is mixed with the solvent at 40°C to 60°C; and / or the concentration of crude cordycepin in the crude cordycepin solution is 30 g / L to 70 g / L; and / or the crude cordycepin solution is cooled, specifically by cooling the temperature to 4 to 10°C at a cooling rate of 3 to 8°C / h; and / or the slurry mother liquor is stabilized at 4 to 10°C for 1 to 4 hours for crystallization; and / or the washing is specifically washing with an ethanol-water solution of less than 70 vt.%; and / or the drying is performed at a drying temperature of 50°C to 60°C; and / or the drying is performed for 10 hours to 12 hours.

[0022] In some embodiments, preferably, the solvent is water.

[0023] In some embodiments, preferably, the concentration of crude cordycepin in the crude cordycepin solution is 40 g / L to 70 g / L, more preferably 40 g / L to 60 g / L.

[0024] In some embodiments, preferably, the crude cordycepin solution is cooled, specifically by cooling the temperature to 4-8°C at a cooling rate of 3-5°C / h.

[0025] In some embodiments, further preferably, the crude cordycepin solution is cooled, specifically by cooling the temperature to 4-6°C at a cooling rate of 3-5°C / h.

[0026] In some embodiments, more preferably, the crude cordycepin solution is cooled, specifically by cooling the temperature to 4°C at a cooling rate of 5°C / h.

[0027] In some embodiments, preferably, the slurry mother liquor is stabilized at 4-8° C. for 1-4 hours for crystallization.

[0028] In some embodiments, further preferably, the slurry mother liquor is stabilized at 4-6° C. for 1-4 hours for crystallization.

[0029] In some embodiments, more preferably, the slurry mother liquor is stabilized at 4° C. for 2 hours for crystallization.

[0030] Among them, the prepared cordycepin crystal form II crystal measured using Cu Kα rays has characteristic diffraction peaks at 5.6°±0.2°, 7.7°±0.2°, 12.2°±0.2°, 14.1°±0.2°, 19.7°±0.2°, and 23.0°±0.2° in terms of 2θ expressed in degrees.

[0031] Among them, preferably, the prepared cordycepin crystalline form II crystals have characteristic diffraction peaks at 5.6°, 7.7°, 12.2°, 14.1°, 19.7°, and 23.0° in a PXRD diffraction pattern expressed in degrees of 2θ measured using Cu Kα rays.

[0032] Furthermore, the present invention discloses a sustained-release tablet comprising

[0033] (i) the cordycepin-oxalate according to above, and

[0034] (ii) pharmaceutically acceptable excipients.

[0035] In some embodiments, the pharmaceutically acceptable excipients include fillers and wetting agents.

[0036] In some embodiments, the filler is any one of microcrystalline cellulose and mannitol or a combination of both; or, the wetting agent is ethanol; or, in the sustained-release tablet, the mass content of the filler is 50% to 70%; or, in the sustained-release tablet, the mass content of cordycepin-oxalate is 30% to 50%.

[0037] In some embodiments, preferably, the filler is a combination of microcrystalline cellulose and mannitol.

[0038] In some embodiments, preferably, when the filler is a composition of microcrystalline cellulose and mannitol, the mass ratio of the microcrystalline cellulose to mannitol is 1.0:(1.2-2.8), more preferably 1.0:(1.5-2.5), and even more preferably 1.0:2.0.

[0039] In some embodiments, preferably, the mass content of the filler in the sustained-release tablet is 55% to 65%.

[0040] In some embodiments, preferably, the mass content of cordycepin-oxalate in the sustained-release tablet is 35% to 45%.

[0041] In some embodiments, the pharmaceutically acceptable excipient further includes a lubricant.

[0042] In some embodiments, when the pharmaceutically acceptable excipient further includes a lubricant, the lubricant is magnesium stearate.

[0043] In some embodiments, when the pharmaceutically acceptable excipient further includes a lubricant, the mass content of the lubricant in the sustained-release tablet is 0.05% to 3.00%.

[0044] There is no special requirement for the dosage of the wetting agent, and the principle of dosage is "it forms a ball when held and falls apart when touched".

[0045] Furthermore, the present invention discloses a method for preparing the sustained-release tablets, comprising mixing the cordycepin-oxalate and the filler, adding the wetting agent to prepare a soft material, sieving to obtain wet granules, drying, and tableting to obtain sustained-release tablets.

[0046] In some embodiments, the screening is through a 10-40 mesh sieve; or, the drying is drying at 40-60° C. and normal pressure for 1-4 hours; or, the diameter of the sustained-release tablet is 5-15 mm; or, the tablet weight of the sustained-release tablet is 0.2-0.6 g.

[0047] In some embodiments, preferably, the sieving is through a 10-30 mesh sieve, preferably through a 20-30 mesh sieve, and more preferably through a 24 mesh sieve.

[0048] In some embodiments, preferably, the drying is carried out at 40-60° C. and normal pressure for 1-2 hours.

[0049] In some embodiments, preferably, the diameter of the sustained-release tablet is 8 to 12 mm, preferably 10 mm.

[0050] In some embodiments, preferably, the sustained-release tablet has a tablet weight of 0.2 to 0.5 g, preferably 0.3 to 0.5 g.

[0051] Beneficial effects:

[0052] (1) The cordycepin of the present invention is obtained by using a water system or a small amount of organic solvent to obtain crystals, thereby avoiding the use of a large amount of organic solvents.

[0053] (2) The cordycepin eutectic salt prepared by the present invention has higher storage stability and slower dissolution rate, which is beneficial to the sustained release effect of the drug.

[0054] (3) The present method is the first to prepare a cordycepin-oxalic acid eutectic salt. The dissolution rate of this cordycepin-oxalic acid eutectic salt is significantly lower than the dissolution rate of cordycepin reported in prior art, and it has extremely high potential for pharmaceutical applications. The sustained-release effect of this cordycepin-oxalic acid eutectic salt has significant technological innovation and market application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more apparent.

[0056] Figure 1 The morphologies of different cordycepin crystals.

[0057] Figure 2 PXRD diffraction patterns of different cordycepin crystals.

[0058] Figure 3 The infrared spectra of different cordycepin crystals.

[0059] Figure 4 The humidity stability data of different cordycepin crystals are shown in the figure.

[0060] Figure 5 Solubility data of different cordycepin crystals.

[0061] Figure 6 The DSC curves of cordycepin monocrystalline form II crystals, ligands, materials obtained by physical mixing, and solid mixtures obtained by liquid-assisted grinding are shown.

[0062] Figure 7 The present invention is a powder X-ray diffraction pattern of cordycepin monocrystalline form II crystals, ligands, materials obtained by physical mixing, and solid mixtures obtained by liquid-assisted grinding.

[0063] Figure 8 This is the infrared spectrum of cordycepin monocrystalline form II crystals, ligands, materials obtained by physical mixing, and solid mixtures obtained by liquid-assisted grinding.

[0064] Figure 9 These are the NMR spectra of different cordycepin cocrystals, cordycepin-oxalate and their raw materials.

[0065] Figure 10 This is a representative liquid phase peak diagram of the standard cordycepin.

[0066] Figure 11 Tablet compression conditions of different cordycepin crystal forms.

[0067] Figure 12 The disintegration diagram of tablets compressed from different cordycepin cocrystals and cordycepin-oxalate. DETAILED DESCRIPTION

[0068] The present invention can be better understood according to the following examples. However, it is easy for those skilled in the art to understand that the contents described in the examples are only used to illustrate the present invention, and should not and will not limit the present invention described in detail in the claims.

[0069] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials are commercially available unless otherwise specified.

[0070] Example 1: Preparation and characterization of cordycepin crystals

[0071] Crude cordycepin was purchased from Nanjing Shenchengyuan Health Technology Co., Ltd. with a purity of >85%.

[0072] 1. Preparation of Cordycepin Anhydrous Form I Crystals

[0073] Dissolve about 20 g / L of crude cordycepin in a 90% isopropanol-water solution at 40° C., then slowly cool the solution to 5° C. at a cooling rate of 3° C. to 5° C. / h. Stable the resulting slurry at 5° C. for 2 h, filter the solution, wash the solid with a 90% isopropanol-water solution, and dry the solution at 50° C. to 60° C. overnight to obtain cordycepin anhydrous Form I crystals with a purity of more than 99%, which are then set aside.

[0074] The water content of the cordycepin anhydrous crystal form I sample was determined by comparing the characteristic peaks of the cordycepin crystal form using JADE 6 software and thermogravimetric analysis (TG) to be 0.11%, which is close to the theoretical water content of the anhydrous crystal (0%) material.

[0075] Crystallographic data of cordycepin anhydrous crystal form I: Chemical formula: C 10 H 13 N5O3; molar mass: 251.25; crystal system: monoclinic; space group: P21; unit cell parameters 4.589(4),7.497(5),16.073(10); unit cell parameters α, β, γ(°): 90, 85.06(10), 90; unit cell volume V 550.9(7); Z: 2; unit cell density (g / cm3): 1.515.

[0076] 2. Preparation of Cordycepin Anhydrous Form II Crystals

[0077] At a temperature of 35°C, about 50 g / L of crude cordycepin was dissolved in a 60% ethanol-water solution, and then the temperature was slowly cooled to 5°C at a cooling rate of 3°C to 5°C / h. The obtained slurry mother liquor was stabilized at 5°C for 2 hours, filtered, and the solid was washed with a 60% ethanol-water solution and dried at 50°C to 60°C overnight to obtain cordycepin anhydrous form II crystals with a purity of more than 99%, which were set aside.

[0078] The water content of the cordycepin anhydrous crystal form II sample was determined by comparing the characteristic peaks of the cordycepin crystal form using JADE 6 software and thermogravimetric analysis (TG), which was 0.05%, close to the theoretical water content of the anhydrous crystal (0%).

[0079] Crystallographic data of cordycepin anhydrous form II crystals: Chemical formula: C 10 H 13 N5O3; molar mass: 251.25; crystal system: orthorhombic; space group: P21212; unit cell parameters 10.231(4),22.752(7),4.817(2); unit cell parameters α, β, γ(°): 90, 90, 90; unit cell volume V 1121.3(7); Z: 4; unit cell density (g / cm3): 1.488.

[0080] 3. Preparation of Cordycepin Crystalline Form II Crystals:

[0081] Under pure water conditions, a crude cordycepin solution with a crude cordycepin concentration of 60 g / L is prepared at 40°C to 60°C, and the temperature is slowly cooled to 4°C at a cooling rate of 5°C / h. The obtained slurry mother liquor is stabilized at 4°C for 2 hours, filtered, and the solid is washed with 70% ethanol aqueous solution and dried at 60°C for 12 hours to obtain cordycepin monocrystalline form II crystals with a purity of more than 99% for standby use.

[0082] The water content of the cordycepin monocrystalline form II crystal sample was determined to be 6.71% by comparing the characteristic peaks of the cordycepin crystal form using JADE 6 software and thermogravimetric analysis (TG), which is close to the theoretical water content of the monohydrate material (6.68%).

[0083] Among them, it has been verified experimentally that the pure water solvent can be replaced with an isopropyl alcohol-water solution below 80 vt.% or an ethanol-water solution below 10 vt.%, and cordycepin crystalline form II crystals can be successfully obtained.

[0084] 4. Characterization of Cordycepin Crystals:

[0085] (1) Observe the sample morphology using TM-3000: Evenly disperse the powder sample with the same particle size on the conductive tape on the circular stage. Since cordycepin does not have conductive properties, the stage is placed in a gold spraying pool to spray gold to enhance the conductivity of the sample. The stage is then fixed in the electron microscope host and the environment is kept in a vacuum state. After the preparation is completed, the sample crystal habits can be observed on the computer workstation and photographed for storage. The morphology of cordycepin crystals is as follows: Figure 1 As shown, Figure a in the figure is the morphology of cordycepin anhydrous crystal type I crystal; Figure b is the morphology of cordycepin anhydrous crystal type II crystal; Figure c is the morphology of cordycepin monocrystalline type II crystal.

[0086] (2) PXRD verification of sample crystal form: Use an agate mortar to grind the sample so that the sample particle size is controlled at 0.1-10μm. Use Bruker D8, Cu Kα radiation, under the conditions of 40KV voltage and 40mA current, scan the 2θ range of 5° to 45° at a rate of 10° / min, and the scanning step is 0.02°. Take an appropriate amount of ground sample and spread it flat in the sample slot and fix the sample slot in the center of the diffractometer host. Scan and obtain the sample diffraction pattern. The PXRD diffraction pattern of cordycepin crystals is as follows: Figure 2 As shown in the figure, the anhydrous cordycepin crystal type I crystal has very obvious high-intensity sharp diffraction peaks at 5.5°, 11.0°, 13.0°, 16.2°, 19.7° and 21.5°. The anhydrous cordycepin crystal type II crystal has very obvious high-intensity sharp diffraction peaks at 7.8°, 9.5°, 11.6°, 14.5°, 15.6° and 23.5°. The crystal characteristic peaks of the two anhydrous cordycepin crystals are consistent with those reported in the literature (Radwan M.M., Wilson HR The structure of cordycepin [J]. Acta Crystallographica Section B, 1980, 36 (9): 2185-2187; Karthe P., Gautham N., Kumar A., ​​et al. [beta]-d-3'-Deoxyadenosine (Cordycepin) [J]. Acta Crystallographica Section C, 1997, 53(11): 1694-1696; Wu Mingsheng, Tang Liang. Analysis of Infrared Spectra and Powder X-ray Diffraction Patterns of Cordycepin Crystals [J]. World Science and Technology (Modernization of Traditional Chinese Medicine), 2011, 13(03): 579-584.). Cordycepin crystal form II has very obvious high-intensity and sharp diffraction peaks at 5.6°, 7.7°, 12.2°, 14.1°, 19.7° and 23.0°.

[0087] (3) Infrared functional group analysis: The results are as follows Figure 3 As shown in the figure (Anhydrate-I is anhydrous cordycepin crystal type I, Anhydrate-II is anhydrous cordycepin crystal type II, and Monohydrate-II is a monocrystalline cordycepin crystal type II), the monocrystalline cordycepin crystal type II is at 3420.04cm -1 The characteristic peaks of crystalline water appear around 3300cm -1 The left and right sides are the stretching vibrations of primary amines ν N-H Peak, 3140-3122cm -1It is the stretching vibration peak of cordycepin-OH, which moves to low frequency due to the easy formation of intramolecular hydrogen bonds, and is lower than the normal ν O-H peak, with increasing intensity and broadening of the spectral band at 2920 cm -1 The stretching vibration peaks of -CH and -CH2 are on the left and right, 1684-1668cm -1 It is the C=N stretching vibration peak on the heterocyclic ring, 1614-1607cm -1 is the deformation vibration of primary ammonia δ N-H , 1100cm -1 The left and right sides are the stretching vibrations of primary alcohols ν O-H Peak. Although the various crystal forms of cordycepin have the same chemical composition, the differences in the arrangement of the crystal structures lead to changes in the unit cell parameters, and the strength of the hydrogen bonds, covalent bonds, etc. between molecules inside the unit cell also changes accordingly. The infrared spectrum is indeed the absorption spectrum caused by the vibration-rotation energy level transition of the molecule, so these changes will inevitably lead to the shift of the functional group position on the infrared spectrum. The infrared characterization of the various crystal forms of cordycepin prepared by the present invention is consistent with the results reported in the literature (Li Zeya, Du Tianyu, Bi Lei, et al. Analysis and detection of cordycepin in culture medium residues by high performance liquid chromatography and infrared spectroscopy [J]. Journal of Beijing Union University, 2020, 34(02): 84-87.).

[0088] (4) Humidity stability evaluation: Weigh 1g of cordycepin crystals, spread them flat in a weighing bottle, and place them in a constant temperature and humidity chamber at 25℃ and different relative humidity (RH). Weigh them regularly and calculate the weight gain percentage to evaluate the hygroscopicity. Figure 4As shown in the figure (Anhydrate-I is a cordycepin anhydrous crystal type I crystal, Anhydrate-II is a cordycepin anhydrous crystal type II crystal, Monohydrate-II is a cordycepin monocrystalline type II crystal, and the relative humidity in Figure a is 43% RH, the relative humidity in Figure b is 63% RH, and the relative humidity in Figure c is 75% RH). According to the Pharmacopoeia 2020 Drug Hygroscopicity Test Guidelines (National Pharmacopoeia Committee. Chinese Pharmacopoeia [M]. Beijing: China Medical Science and Technology Press, 2020.), it can be known that: cordycepin anhydrous crystal type I crystals gain 0.80% at 43% RH, with almost no hygroscopicity, gain 3.61% at 63% RH, with hygroscopicity, and gain 20.92% at 75% RH, with strong hygroscopicity and greatly affected by ambient humidity. It is saturated with adsorption after 400h; cordycepin anhydrous crystal type II crystals gain 0.24% at 43% RH, with almost no hygroscopicity, and gain 0.1% at 63% RH. The weight gain of cordycepin monocrystalline form II crystals was 1.27% under RH conditions and was slightly hygroscopic. The weight gain of cordycepin monocrystalline form II crystals was 9.00% under RH conditions and was hygroscopic. The crystals were less affected by environmental humidity than cordycepin anhydrous form I crystals and reached adsorption saturation after 200 hours. The weight gain of cordycepin monocrystalline form II crystals was 4.07% under RH conditions and was hygroscopic. The weight gain of cordycepin monocrystalline form II crystals was 4.18% under RH conditions and was hygroscopic. The weight gain of cordycepin monocrystalline form II crystals was 5.80% under RH conditions and was hygroscopic, but was not greatly affected by environmental humidity. Adsorption saturation was basically reached after 200 hours, and the weight gain percentage was stable at about 4%. The crystals were least affected by environmental humidity. Cordycepin monocrystalline form II crystals had the highest humidity stability and were easy to store.

[0089] (5) Solubility determination: The solubility of cordycepin was determined by the static method. The specific operation is as follows:

[0090] (1) Prepare three aqueous solutions in 25 mL Erlenmeyer flasks. The solubility changes between 298.5 K and 325 K. The flasks are sealed and stored.

[0091] (2) Add excess cordycepin crystals into the above-mentioned flasks, and place the flasks in a constant temperature water bath with a magnetic stirring function.

[0092] (3) To ensure that the cordycepin crystals reach solid-liquid equilibrium and are fully dissolved at this temperature, the stirring speed is controlled at 150 rpm and stirred for at least 6 hours; at the same time, to ensure sufficient solid-liquid phase separation, the magnetic stirring function is turned off and the mixture is kept at a constant temperature for at least 3 hours.

[0093] (4) A high-precision syringe was used to transfer an appropriate amount of supernatant, filtered through an organic membrane with a pore size of 0.22 μm, and diluted to a certain multiple. The concentration was then determined using an ultraviolet spectrophotometer. Each group of experiments was repeated three times and the average value was taken.

[0094] Specific experimental results can be found in Figure 5 As can be seen in the figure (Anhydrate-I is anhydrous cordycepin Form I, Anhydrate-II is anhydrous cordycepin Form II, and Monohydrate-II is monocrystalline cordycepin Form II), the solubility of each crystalline form of cordycepin increases with increasing temperature, indicating that cordycepin dissolution is a typical endothermic process. Among them, monocrystalline cordycepin Form II has the lowest solubility of the three crystalline forms.

[0095] In summary, cordycepin crystalline form II crystals have the characteristics of lowest solubility and good humidity stability. Therefore, cordycepin crystalline form II crystals were used as raw materials to prepare cocrystals.

[0096] Example 2: Preparation and characterization of cordycepin cocrystals

[0097] 1. Preparation of Cordycepin Cocrystal or Cordycepin-Ligand Salt

[0098] (1) Physical mixing: 10 mmol of the ligand and 10 mmol of cordycepin monocrystalline form II crystals (prepared in Example 1) were mixed thoroughly;

[0099] (2) Liquid-assisted grinding: 1 mL of pure water was added as an auxiliary agent and the mixture was ground continuously in an agate mortar for 1.5 h to obtain a solid mixture;

[0100] (3) After grinding, the solid mixture is dried at normal pressure and 40° C. for 8 to 12 hours to obtain a cordycepin cocrystal or a cordycepin-ligand salt.

[0101] The ligands were oxalic acid, gallic acid, or vanillic acid, respectively, to prepare cordycepin-oxalate (with a molar ratio of 1:1), cordycepin-gallic acid cocrystal (with a molar ratio of 1:1), and cordycepin-vanillic acid cocrystal (with a molar ratio of 1:1). The molar ratio of cordycepin to ligand in each cordycepin cocrystal or cordycepin-ligand salt was calculated using liquid phase mass balance. The cordycepin content of 1 g of the cordycepin cocrystal compound was measured using liquid phase analysis. The calculated mass of 1 g was based on a 1:1 molar ratio of cordycepin to ligand.

[0102] Among them, the cordycepin cocrystal or cordycepin-ligand salt can also be successfully obtained by replacing the pure water in step (2) with an ethanol-water solution of less than 10 vt.% or an isopropanol-water solution of less than 10 vt.%.

[0103] 2. Characterization of Cordycepin Cocrystals or Cordycepin-Ligand Salts

[0104] (1) Thermal analysis: Using differential scanning calorimetry, cordycepin monocrystalline form II crystals (dA-original), oxalic acid, gallic acid, vanillic acid, the material obtained by physical mixing of cordycepin-oxalate, cordycepin-gallic acid cocrystal, and cordycepin-vanillic acid cocrystal (PM), and the solid mixture obtained by liquid-assisted grinding (LGA-Water) were dried at 100°C for 1-2 hours to remove surface adsorbed water, and then the samples were characterized by thermal analyzer. The measurement results are shown in Figure 2. Figure 6 As shown in the figure (Figure a shows the relevant components of cordycepin-oxalate prepared with oxalic acid as raw material; Figure b shows the relevant components of cordycepin-gallic acid cocrystal prepared with gallic acid as raw material; Figure c shows the relevant components of cordycepin-vanillic acid cocrystal prepared with vanillic acid as raw material), it can be seen from the DSC curve that three endothermic peaks appear after the physical mixing of cordycepin and oxalic acid. The first one at 62.04°C is the endothermic peak of monohydrate dehydration of cordycepin, the third one at 172.25°C is the melting point endothermic peak of cordycepin, which is 27°C lower than that of the pure product, and the second one at 111.46°C is the melting point of oxalic acid itself, which is 10°C higher than that of the pure oxalic acid. It is speculated that the blend has a slight effect on the melting of each substance, and a new single melting point appears after liquid-assisted grinding. At 159.01°C, the melting point is between the two monomers of cordycepin and oxalic acid, and is also different from the melting point of the two components physically mixed. Therefore, it can be known that the two components after grinding are indeed a new salt, namely cordycepin-oxalate (Figure a); the two components of the physical mixture of cordycepin and gallic acid still have two melting points of cordycepin at 101.34°C and 155.71°C. It is speculated that the influence of the mixture causes the melting point of gallic acid to rise to 81.83°C, and the melting point of cordycepin is lowered to 155.71°C (Figure b); the mixture of cordycepin and vanillic acid has two melting points at 103.52°C and 206.7°C, while the new substance eutectic obtained after liquid-assisted grinding has only one fixed melting point of 197.43°C (Figure c).

[0105] (2) Powder X-ray diffraction patterns (PXRD patterns): X-ray diffraction patterns of cordycepin monocrystalline form II crystals (dA original), oxalic acid, gallic acid, vanillic acid, the material obtained by physical mixing of cordycepin-oxalate, cordycepin-gallic acid cocrystal, and cordycepin-vanillic acid cocrystal (PM), and the solid mixture obtained by liquid-assisted grinding (LGA-Water) were measured. The measurement results are shown in Figure 2. Figure 7 As shown in the figure (Figure a shows the relevant components of cordycepin-oxalate prepared using oxalic acid as raw material; Figure b shows the relevant components of cordycepin-gallic acid cocrystal prepared using gallic acid as raw material; Figure c shows the relevant components of cordycepin-vanillic acid cocrystal prepared using vanillic acid as raw material), it can be seen from the figure that cordycepin forms a new phase with oxalic acid, gallic acid and vanillic acid at a molar ratio of 1:1, and the crystals assisted by LGA grinding have obvious diffraction peaks at a 2θ angle of 25 degrees, indicating that cordycepin cocrystal or cordycepin-oxalate is successfully obtained.

[0106] (3) Infrared spectroscopy analysis: Fourier transform infrared spectroscopy (FTIR) was used to determine the infrared spectrum of the cordycepin cocrystal. Cordycepin monocrystalline form II crystals (dA original), oxalic acid, gallic acid, vanillic acid, the material obtained by physically mixing cordycepin-oxalate, cordycepin-gallic acid cocrystal, and cordycepin-vanillic acid cocrystal (PM), and the solid mixture obtained by liquid-assisted grinding (LGA-Water) were subjected to infrared measurements. The results are shown in Table 1. Figure 8 The infrared spectrum of cordycepin crystal type II crystals has a peak wavenumber and intensity between 4000 and 500. After sufficient physical grinding, the peak wavenumber and intensity of LGA-Water are obviously different from those of the pure product and the material obtained by simple physical mixing, which can prove that a copolymerization reaction occurs and the vibration and stretching of the chemical bond changes, proving that copolymers of cordycepin and ligands can be produced under assisted grinding.

[0107] (4) Nuclear magnetic resonance analysis: Use nuclear magnetic resonance to determine the monomer nuclear magnetic resonance and cocrystal of cordycepin and ligand substances, and compare the analysis results. Figure 9 As shown in the figure (dA is a cordycepin crystal form II, OA is oxalic acid, dA-OA is cordycepin-oxalate, GA is gallic acid, dA-GA is a cordycepin-gallic acid cocrystal, VA is vanillic acid, and dA-VA is a cordycepin-vanillic acid cocrystal; Figure a is the H NMR spectrum of cordycepin-oxalate and the raw material, Figure d is the C NMR spectrum of cordycepin-oxalate and the raw material; Figure b is the H NMR spectrum of cordycepin-gallic acid cocrystal and the raw material, Figure e is the C NMR spectrum of cordycepin-gallic acid cocrystal and the raw material; Figure c is the H NMR spectrum of cordycepin-vanillic acid cocrystal and the raw material, and Figure f is the C NMR spectrum of cordycepin-vanillic acid cocrystal and the raw material), the shift of the characteristic peak is indicated by "*".

[0108] NMR 1H spectrum measurement shows that as shown in Figures a, b, and c, Figure a shows that the H spectrum of the dA-OA pseudo-eutectic has no peak near 11ppm-12ppm, while OA itself has a carboxyl H peak at 11.31ppm, indicating that the H on the carboxyl group is lost, that is, proton transfer occurs, and cordycepin and oxalic acid form salts; Figures b and c show that the dA-GA pseudo-eutectic and dA-VA pseudo-eutectic have carboxyl H peaks at 12.24ppm and 12.43ppm, respectively, and the pseudo-eutectic H spectrum is the superposition of two monomers, so both of them form cordycepin-ligand binary eutectics, and through integral quantification, it can be seen that the stoichiometric ratio of the two is 1:1. The C NMR spectra of dA-OA, dA-GA, and dA-VA are shown in Figures d, e, and f. It can be seen that the carbonyl carbon of dA-OA is at 161.88 ppm, which is 0.57 ppm shifted downfield relative to the carbonyl carbon of OA at 161.31 ppm; the carbonyl carbon of dA-GA is at 167.92 ppm, which is almost not shifted relative to the carbonyl carbon of GA at 167.91 ppm; the carbonyl carbon of dA-VA is at 167.68 ppm, which is almost not shifted relative to the carbonyl carbon of VA at 167.66 ppm.

[0109] Example 3: In vitro dissolution experiment of cordycepin polymorphs and co-crystals

[0110] 1. Tablet formula and preparation method

[0111] The dissolution experiment of cordycepin polymorphs and cocrystals was conducted using the most commonly used oral tablet dosage form. Microcrystalline cellulose (20%), mannitol (40%), and magnesium stearate (1%) were selected as auxiliary solvents. Ethanol was used as the auxiliary solvent and then dried at 50°C for removal. The main drugs (cordycepin anhydrous crystal form I crystals prepared in Example 1, cordycepin anhydrous crystal form II crystals prepared in Example 1, cordycepin monocrystalline form II crystals prepared in Example 1, cordycepin-oxalate prepared in Example 2, cordycepin-gallic acid cocrystals prepared in Example 2, and cordycepin-vanillic acid cocrystals prepared in Example 2, accounting for 39%) and auxiliary materials were weighed, crushed, sieved, and mixed. Ethanol was added as a binder to prepare a soft material, which was then passed through a 24-mesh sieve to prepare wet granules of 0.8 mm in size. The granules were dried at 40°C under normal pressure for 1 hour to remove residual ethanol, and then compressed on a multi-punch tablet press to obtain tablets with a diameter of 10 mm and a tablet weight of 0.45 g.

[0112] 2. Dissolution medium configuration and sampling point design

[0113] According to the second method of dissolution determination in the general rules of Part IV of the 2020 edition of the "Chinese Pharmacopoeia", 900 mL of the dissolution medium after ultrasonic degassing was taken. In this experiment, two dissolution media, pH = 1.2 hydrochloric acid solution and pH = 6.8 phosphate buffer, were selected to simulate artificial gastric juice and artificial intestinal juice for dissolution test. When the temperature of the dissolution medium was constant at 37 ± 0.5 ° C and the speed was 75 r / min, 6 cordycepin tablets were put into the dissolution cup and the time was immediately started. 2 mL of the dissolution medium volume was sampled at 5min, 10min, 15min, 30min, 45min, and 60min respectively. After sampling, the isothermal and equal volume dissolution medium was added. After the taken out dissolution medium was treated with a 0.22μm microporous filter membrane, the cordycepin content was determined according to HPLC chromatographic conditions. Among them, the HPLC chromatographic conditions are as follows: quantification: external standard method (standard cordycepin, Nanjing Life Original Health Technology Co., Ltd., batch number GXD20220601, amorphous powder, purity more than 98%); separation column: 880975-914SB-Aq, 4.6 mm × 250 mm, 5 μm; detection instrument: Agilent 1260; detection wavelength: 254 nm; injection volume: 20 μL; flow rate: 1.0 μL / min; column temperature: 30 ° C; isocratic elution; mobile phase: potassium dihydrogen phosphate (0.01 mol / L): methanol = 75:25, passed through a 0.22 μm filter membrane and degassed before use.

[0114] 3. Tablet hardness test

[0115] Before dissolution testing of cordycepin tablets produced by a tablet press, the tablet's hardness needs to be measured. Tablets should be sufficiently hard to prevent breakage or abrasion during packaging and transportation, ensuring accurate dosing. Several methods exist for measuring and expressing tablet hardness. The YD-35 tablet hardness tester is a commonly used laboratory instrument for tablet hardness measurement, measuring both tablet hardness and diameter. This study used crushing strength to characterize tablet hardness. A cordycepin tablet was placed upright between the two platens of the YD-35 tablet hardness tester. Pressure was applied along the tablet's diameter, and the pressure required to break the tablet was measured as its crushing strength.

[0116] 4. Experimental results

[0117] (1) Liquid phase concentration test results

[0118] Under the detection conditions, the retention time of the standard cordycepin is 16.4 min, so according to the determination, the standard curve y=0.0162x-0.106, R 2 =1, used to calculate the actual cordycepin release concentration corresponding to the retention time of different cordycepin crystal forms and different cordycepin co-crystals. The representative liquid phase peak diagram of standard cordycepin is shown in Figure 10 .

[0119] (2) Dissolution data and disintegration of tablets prepared from cordycepin polymorphs

[0120] After tableting with a multi-punch tablet press, tablets with a diameter of 10 mm, a tablet weight of 0.45 g / tablet, and a hardness of about 50 N were obtained. During the dissolution test, the tablets of different cordycepin crystal forms were as follows Figure 11 As shown in the figure (Figure a is a tablet pressed from cordycepin anhydrous crystalline Form I crystals; Figure b is a tablet pressed from cordycepin anhydrous crystalline Form II crystals; Figure c is a tablet pressed from cordycepin monocrystalline Form II crystals), it can be seen from the figure that the tablets pressed from cordycepin anhydrous crystalline Form I crystals have obvious "oiling" phenomenon, which is speculated to be because the cordycepin anhydrous crystalline Form I crystals are unstable and phase change under high pressure leads to "oiling", and in the hardness test, it shows a fluctuation of 50±4N; while the tablets pressed from cordycepin anhydrous crystalline Form II crystals and the tablets pressed from cordycepin monocrystalline Form II crystals are no different, and the hardness is stable at 50N, indicating that the cordycepin anhydrous crystalline Form II crystals and cordycepin monocrystalline Form II crystals have good compressibility.

[0121] Tables 1 and 2 show the dissolution data for three cordycepin polymorphs in artificial gastric fluid (pH = 1.2) and artificial intestinal fluid (pH = 6.8). As shown in Tables 1 and 2, cordycepin anhydrous crystal Form I is the most sustained-release crystal form, with complete release occurring after 60 minutes. However, fluctuations in its hardness and oil release may affect its disintegration and release, making this crystal form unsuitable for sustained-release medication. Cordycepin anhydrous crystal Form II releases completely after 10 minutes, a relatively rapid release rate that contradicts the initial sustained-release objective of the present invention. Cordycepin monocrystalline Form II can delay release until complete disintegration and release occurs after 30 minutes, making it the optimal crystal form for sustained-release medication. This further supports the aforementioned consideration of preparing a sustained-release cocrystal from cordycepin monocrystalline Form II. The three crystal forms also share a common dissolution characteristic: faster release in gastric fluid than in intestinal fluid, primarily because cordycepin is a purine alkaloid with better solubility at low pH.

[0122] Table 1 Dissolution data of tablets compressed from three cordycepin polymorphs in artificial gastric fluid (pH = 1.2)

[0123]

[0124]

[0125] Table 2 Dissolution data of tablets compressed from three cordycepin polymorphs in artificial intestinal fluid (pH = 6.8)

[0126]

[0127] (3) Dissolution data and disintegration of tablets prepared from cordycepin cocrystals

[0128] (3-1) Different disintegration conditions: See the diagram for specific disintegration conditions. Figure 12 Figure a shows the disintegration of cordycepin-oxalate compressed tablets in simulated gastric fluid (pH 1.2), Figure b shows the disintegration of cordycepin-oxalate compressed tablets in simulated intestinal fluid (pH 6.8), Figure c shows the disintegration of cordycepin-gallic acid cocrystal compressed tablets in simulated gastric fluid (pH 1.2), Figure d shows the disintegration of cordycepin-gallic acid cocrystal compressed tablets in simulated intestinal fluid (pH 6.8), Figure e shows the disintegration of cordycepin-vanillic acid cocrystal compressed tablets in simulated gastric fluid (pH 1.2), and Figure f shows the disintegration of cordycepin-vanillic acid cocrystal compressed tablets in simulated intestinal fluid (pH 6.8). As can be seen from the figures, the disintegration of tablets in each group is consistent, and the disintegration and release rate is gastric fluid (pH 1.2) > intestinal fluid (pH 6.8), which is consistent with the release of tablets compressed from cordycepin polymorphic crystals, mainly due to the properties of cordycepin alkaloids themselves. By comparison, it was found that (a) cordycepin-oxalate compressed tablets were completely released in artificial gastric juice at 30 minutes, but could be sustained in artificial intestinal juice for up to 50 minutes. At this time, there were still "small grain piles" of drug residues after disintegration, which was the slowest group of tablets in disintegration and release. The release was longer than the 30 minutes of cordycepin-crystal II compressed tablets, indicating that a sustained release effect is expected to be achieved; (b) cordycepin-oxalate compressed tablets were completely released in artificial gastric juice at 30 minutes, but could be sustained in artificial intestinal juice for up to 50 minutes. At this time, there were still "small grain piles" of drug residues after disintegration, which was the slowest group of tablets in disintegration and release. Tablets compressed from the cordycepin-gallic acid cocrystal completed release in 20 minutes in both artificial intestinal and artificial gastric fluids, demonstrating a delayed release effect compared to tablets compressed from cordycepin-free crystalline Form II crystals. However, this effect was not as strong as that achieved by tablets compressed from cordycepin-crystalline Form II crystals, indicating that the cordycepin-gallic acid cocrystal failed to achieve sustained release. (c) Tablets compressed from the cordycepin-vanillic acid cocrystal completed release at 30 minutes, similar to tablets compressed from cordycepin-crystalline Form II crystals, indicating that the release rate of cordycepin was not slowed. In contrast, cordycepin-oxalate salt was identified as a salt with the potential to exhibit significant sustained release in artificial intestinal fluid.

[0129] (3-2) Comparison of dissolution data: The dissolution data are shown in Tables 3 and 4. From the data in the tables, it can be seen that only the tablets compressed with cordycepin-oxalate have a more obvious sustained-release effect. The release is completed in 30 minutes in artificial gastric fluid, and can be extended to 50 minutes in artificial intestinal fluid, showing a significant sustained-release effect. At the same time, the dissolution rate is slow at first and then fast, which is a non-constant release pattern. The cordycepin-gallic acid cocrystal shows a rapid release effect (20 minutes) compared with cordycepin crystal form II (30 minutes). The same is true for cordycepin-vanillic acid, but it is slightly better than cordycepin-gallic acid, slowing down the disintegration and release by 5 minutes.

[0130] Table 3 Dissolution data of three cordycepin cocrystal tablets in artificial gastric fluid (pH = 1.2)

[0131]

[0132]

[0133] Table 4 Dissolution data of three cordycepin cocrystal compressed tablets in artificial intestinal fluid (pH = 6.8)

[0134]

[0135] In summary, oxalic acid can effectively slow-release cordycepin, and the slow-release effect is best in intestinal fluid.

[0136] The present invention provides a cordycepin-oxalate salt, its preparation method, and its application. Numerous methods and approaches exist for implementing this technical solution. The foregoing description is merely a preferred embodiment of the present invention. It should be noted that those skilled in the art may make various improvements and modifications without departing from the principles of the present invention, and such improvements and modifications are also within the scope of protection of the present invention. Any components not specified in this embodiment may be implemented using existing technologies.

Claims

1. A cordycepin-oxalate, characterized in that: The molecular formula of the cordycepin-oxalate is C 10 H 13 N5O3·H2C2O4; the molecular structure of the cordycepin-oxalate is as follows:

2. The method for preparing cordycepin-oxalate according to claim 1, characterized in that: The steps include: (1) Physical mixing: Take oxalic acid and cordycepin-crystalline form II crystals and mix them thoroughly; (2) Liquid-assisted grinding: Add additives and continue grinding to obtain a solid mixture; (3) Drying the solid mixture to obtain cordycepin-oxalate.

3. The preparation method according to claim 2, characterized in that In step (1), the molar ratio of oxalic acid to cordycepin-type II crystals is 1:1; or, In step (2), the auxiliary agent is water, 10 vol.% or less ethanol-water solution or 10 vol.% or less isopropanol-water solution; and / or the mass of the auxiliary agent is 20% to 70% of the total mass of the oxalic acid and cordycepin monocrystalline form II crystals; and / or the grinding time is 1.0 to 8.0 hours; or In step (3), the drying is carried out under normal pressure; and / or the drying is carried out at 40 to 60° C.; and / or the drying time is 8 to 12 hours.

4. The preparation method according to claim 2, characterized in that In step (1), the cordycepin monocrystalline form II crystals are prepared according to the following method: The crude cordycepin is mixed with a solvent to obtain a crude cordycepin solution; the crude cordycepin solution is cooled, and the obtained slurry mother liquor is stabilized and crystallized, which is then filtered, the solid is washed, and dried to obtain cordycepin monocrystalline form II crystals.

5. The preparation method according to claim 4, characterized in that The solvent is water, an isopropanol-water solution of less than 80 vt.%, or an ethanol-water solution of less than 10 vt.%; and / or the crude cordycepin is mixed with the solvent at 40°C to 60°C; and / or the concentration of crude cordycepin in the crude cordycepin solution is 30g / L to 70g / L; and / or the crude cordycepin solution is cooled, specifically by cooling the temperature to 4-10°C at a cooling rate of 3-8°C / h; and / or the slurry mother liquor is stabilized at 4-10°C for 1-4h for crystallization; and / or the washing is specifically performed using an ethanol-water solution of less than 70 vt.%; and / or the drying is performed at a drying temperature of 50°C to 60°C; and / or the drying is performed for 10h to 12h.

6. A sustained-release tablet, characterized in that Include (i) the cordycepin-oxalate according to claim 1, and (ii) pharmaceutically acceptable excipients.

7. The sustained-release tablet according to claim 6, characterized in that The pharmaceutically acceptable excipients include fillers and wetting agents.

8. The sustained-release tablet according to claim 7, characterized in that The filler is any one of microcrystalline cellulose and mannitol or a combination of both; or the wetting agent is ethanol; or the mass content of the filler in the sustained-release tablet is 50% to 70%; or the mass content of cordycepin-oxalate in the sustained-release tablet is 30% to 50%.

9. The method for preparing the sustained-release tablet according to claim 7, characterized in that: The cordycepin-oxalate according to claim 1 and the filler are mixed, and the wetting agent is added to prepare a soft material, which is sieved to obtain wet granules, dried, and tableted to obtain sustained-release tablets.

10. The preparation method according to claim 9, characterized in that The sieving is through a 10-40 mesh sieve; or, the drying is drying at 40-60° C. and normal pressure for 1-4 hours; or, the diameter of the sustained-release tablet is 5-15 mm; or, the tablet weight of the sustained-release tablet is 0.2-0.6 g.

Citation Information

Cited By

  • Cordycepin-oxalate, and preparation method therefor and application thereof

    GB2702042A